Advanced heart failure due to coronary aneurysms - Estupiñán-Paredes, Ruth N. (2022)
We present the case of a 61 years old man with hypothyroidism, hypertension, type 2 diabetes mellitus, and ischemic cardiopathy, who was admitted with a diagnosis of non-ST elevation myocardial infarction. The coronary angiography describes coronary ectasia with giant aneurysm and slow flow in the right coronary and aneurysm with slow flow anterior descending coronary. The echocardiogram shows contractility disorders with severely decreased left ventricular ejection fraction (20%) despite optimal medical management. This case presents a patient with ischemic heart disease and advanced heart failure secondary to coronary aneurysm, the proposed optimal treatment was a heart transplant given the disease’s progression.